Arabidopsis TWISTED DWARF1 regulates stamen elongation by differential activation of ABCB1, 19-mediated auxin transport. (5th May 2022) - Liu, Jie; Ghelli, Roberta; Cardarelli, Maura; Geisler, Markus
Abstract : We demonstrate an essential role for the FKBP42, TWISTED DWARF1, in the regulation of stamen elongation. This is achieved by differential activation of ABCB-mediated auxin transport during stamen development. Abstract: Despite clear evidence that a local accumulation of auxin is likewise critical for male fertility, much less is known about the components that regulate auxin-controlled stamen development. In this study, we analyzed physiological and morphological parameters in mutants of key players of ABCB-mediated auxin transport, and spatially and temporally dissected their expression on the protein level as well as auxin fluxes in the Arabidopsis stamens. Our analyses revealed that the FKBP42, TWISTED DWARF1 (TWD1), promotes stamen elongation and, to a lesser extent, anther dehiscence, as well as pollen maturation, and thus is required for seed development. Most of the described developmental defects in twd1 are shared with the abcb1 abcb19 mutant, which can be attributed to the fact that TWD1—as a described ABCB chaperone—is a positive regulator of ABCB1- and ABCB19-mediated auxin transport. However, reduced stamen number was dependent on TWD1 but not on investigated ABCBs, suggesting additional players downstream of TWD1. We predict an overall housekeeping function for ABCB1 during earlier stages, while ABCB19 seems to be responsible for the key event of rapid elongation at later stages of stamen development. Our data indicate that TWD1 controls stamen development by differential activation of ABCB1, 19-mediated auxin transport in the stamen.